Direct and indirect costs associated to type 2 diabetes and its complications measured in a social security institution of Argentina - Elgart, Jorge Federico (2014)
Objectives To estimate direct and indirect costs of care of type 2 diabetes (T2DM) and its complications in Argentina, and compare them with those recorded in people without diabetes (ND). Methods: Observational retrospective case–control study performed in one institution of the Social Security System of Argentina. Participants were identified and randomly selected from the Institution’s electronic medical records. We recruited persons with T2DM with (387) or without (387) chronic complications and 774 ND, matched by age and gender. Data were obtained by telephone interviews and supplemented with data from the Institution’s records. Parametric and non-parametric tests were used for group comparisons. Results: Direct costs were higher in people with T2DM than in ND: twice as high in people with T2DM without complications and 3.6 times in those with complications. Absenteeism was only higher in T2DM with complications, but there were no differences among groups either in the duration or in the cost of such absenteeism. Conclusions: T2DM and the development of its complications are positively associated with higher direct costs in Argentina.